2020
DOI: 10.5187/jast.2020.62.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Replacement value of cottonseed meal for soybean meal in broiler chicken diets with or without microbial enzymes

Abstract: A 4×2 factorial feeding trial was designed to investigate the effect of replacing soybean meal (SBM) with cottonseed meal (CSM) in wheat/sorghum/SBM-based diets fed with or without microbial enzymes in diets on the performance, visceral organ development and digestibility of nutrients of broiler chickens. Four graded levels of CSM -none (0%), low (4%, 8%, and 12%), medium (5%, 10%, and 15%), and high (6%, 12%, and 18%) of complete diets in starter, grower and finisher, respectively were fed with or without 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…It was previously reported that incorporating a xylanase and βglucanase in a diet based on corn-and wheat increased starch digestibility [39], this may be due to the role of β-gluca-nase and xylanase in releasing more unavailable nutrients from cell walls existing in many dietary ingredients [40]. Digestibility of CP enhanced by test enzyme in this study as part of enzyme activity on reducing the negative impact of gossypol, which supports [41] result who concluded that CP and starch digestibility increased in broiler chickens fed CSM-containing diets with xylanase and β-glucanase blend.…”
Section: Apparent Ileal Digestibility Of Nutrientssupporting
confidence: 82%
“…It was previously reported that incorporating a xylanase and βglucanase in a diet based on corn-and wheat increased starch digestibility [39], this may be due to the role of β-gluca-nase and xylanase in releasing more unavailable nutrients from cell walls existing in many dietary ingredients [40]. Digestibility of CP enhanced by test enzyme in this study as part of enzyme activity on reducing the negative impact of gossypol, which supports [41] result who concluded that CP and starch digestibility increased in broiler chickens fed CSM-containing diets with xylanase and β-glucanase blend.…”
Section: Apparent Ileal Digestibility Of Nutrientssupporting
confidence: 82%
“…Non-starch polysaccharide-degrading enzymes (mainly xylanase and β-glucanase) are increasingly being used in combination with phytase to improve fiber digestion in diets containing RSM, with variable results. Mushtaq et al (2007) reported no significant effect of a xylanase–β-glucanase combination added to corn and SBM-based diets containing 2 levels of RSM (20% and 30%) on growth performance during 0 to 42 d of age, whereas the study by Abdallh et al (2020) reported that xylanase–β-glucanase supplementation of diets containing 3 levels of CSM as a replacement for SBM (up to a maximum of 6, 12, and 18% CSM in starter, grower and finisher phases) improved FCR and increased weight gain in grower and finisher phases compared to unsupplemented diets. Meanwhile, protease can improve protein digestibility, particularly in low CP diets ( Angel et al, 2011 ; Mohammadigheisar and Kim, 2018 ).…”
Section: Introductionmentioning
confidence: 92%
“…In wholly vegetable diets, SBM-alternatives must be plant-based, deliver a similar digestible AA profile in the total ration to diets based on SBM and exhibit a proven capacity to maintain growth performance when used in commercial diets. Potential alternatives include rapeseed meal ( RSM ; in some regions referred to as canola meal [ CM ; Mushtaq et al, 2007 ; Xu et al, 2012 ; Payvastegan et al, 2017 ]), sunflower meal ( SFM ; Rama Rao et al, 2006 ; de Morais Oliveira et al, 2016 ), cottonseed meal ( CSM ; Abdallh et al, 2020 ), linseed meal ( Tamasgen et al, 2021 ), peas ( Bingol et al, 2016 ) and potato meal ( Sultana et al, 2016 ). Most studies to date have investigated the effect of partial rather than total SBM replacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean meal is a by-product of the production of soybean oil, which has a high protein content, and it is widely used to manufacture animal feed and produce soy concentrate and antibiotics [ 24 , 25 ]. Soybean meal is the main economic component of soybean and accounts for 60% of its value [ 26 ]. Soybean meal, a cheap source of organic nitrogen, is a fermentation substrate with great potential.…”
Section: Introductionmentioning
confidence: 99%